2015
DOI: 10.1111/jonm.12323
|View full text |Cite
|
Sign up to set email alerts
|

The role of professional and team commitments in nurse-physician collaboration

Abstract: Inter-professional collaboration is affected by the relationship between physicians and nurse at the professional group level. Managers who want to change and improve inter-professional collaboration should pay close attention to the interplay between changes they are introducing and well-established identities and practices between professionals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 38 publications
0
11
0
1
Order By: Relevance
“…Professional autonomy is the legitimate control that the members of an occupation exercise over the organization and the terms of their work [ 14 ]. Individual-level studies of physicians’ autonomy inside organizations have examined professional autonomy in different domains [ 15 , 16 ]. Following these and other studies, we identified three main dimensions of autonomy: 1) clinical work freedom, 2) social and economic work freedom, and 3) influence on organizational decisions.…”
Section: Professional Autonomy Of Physiciansmentioning
confidence: 99%
“…Professional autonomy is the legitimate control that the members of an occupation exercise over the organization and the terms of their work [ 14 ]. Individual-level studies of physicians’ autonomy inside organizations have examined professional autonomy in different domains [ 15 , 16 ]. Following these and other studies, we identified three main dimensions of autonomy: 1) clinical work freedom, 2) social and economic work freedom, and 3) influence on organizational decisions.…”
Section: Professional Autonomy Of Physiciansmentioning
confidence: 99%
“…This may depend on barriers in organization or inter-professional collaborations at PHCs, which are important factors for providing optimal asthma care (3,33,120,121). For successful inter-professional collaborations, the interplay between nurses and physicians is of importance (122), where knowledge and trust of competence among colleagues can support the feeling of being a team (123).…”
Section: Adherence To Guidelines (Studies I Ii Iii and Iv)mentioning
confidence: 99%
“…Organisation management can be considered to have an effect on cooperation. In the case of a nurse, there are reports that commitment to the care unit has a significant positive effect on the attitude towards collaboration among professionals [25], so that nurse-physician collaboration should be regarded as a concern for the whole organisation.…”
Section: Attitude As a Team Of Physician And The Nursementioning
confidence: 99%